Research in the Social Scientific Study of Religion, Volume 32 : Lesser Heard Voices in Studies of Religion - Hood, Ralph W.; Cheruvallil-Contractor, Sariya (Research in the Social Scientific Study of Religion, 2022)
The present volume brings together scholars from all over the world in an open section and three special sections that explore how lesser-heard and unheard voices may be studied. Special section 1, Religion in Higher Education interrogates lived experiences of religion in higher education contexts and how certain voices are marginalised and minoritised. Special section 2, Cultural Blindness in Psychology, explores how culture as a lived experience, especially in its religious dimension, is rendered invisible in psychological science. Finally, special section 3 entitled Religious Authority in Practice in Contemporary Evangelical, Charismatic, and Pentecostal Christianity outlines "evangelicalism" and introduces "authority" as a sociological concept from various theoretical perspectives.